Effects of Organic Amendments and Mineral Fertilizers on Optimizing Nutrient Cycling in Alkaline Soil (Plant Bulletin, 2024)
Soil microbial biomass carbon (MBC) and nitrogen (MBN) are indicators of microbial size and soil fertility, representing a vital living nutrient reservoir in the soil. This study aimed to evaluate the impact of various organic sources, such as poultry manure (PM), farmyard manure (FYM), compost (CM), and biochar (BC), along with different levels of mineral fertilizers on soil microbial dynamics and nutrient (N, P) mineralization through laboratory incubation experiments. The organic amendments were applied at rates of 0.25%, 0.5%, and 1.0% of soil carbon (w/w), combined with 75%, 50%, and 25% of recommended doses of NPK (120:90 and 60 kg N, P2O5, and K2O ha-1), respectively. Following the application of amendments, the soil underwent a 16-day incubation period to measure CO2 emissions and a 28-day period for N and P mineralization. The rate of CO2 evolution exhibited a significant increase with higher carbon levels but declined over time. Compost showed the highest CO2 evolution at any given time, followed by PM, FYM, and BC, likely due to a higher readily available fraction of carbon. Compost, particularly at the 1% C level in combination with inorganic fertilizer, led to a significant increase in soil microbial biomass C and N. Nitrogen and phosphorous mineralization increased with the duration of the 28-day incubation period. However, the net release of N and P decreased with higher carbon levels, potentially associated with both immobilization and the fact that higher levels received lower (25%) NPK levels. Nevertheless, soils treated with CM and PM maintained higher levels of N and P, associated with their higher fraction of labile nutrients. These findings suggest that the continuous application of organic sources enhances N and P mineralization, soil microbial biomass, and their activity. Therefore, the regular application of carbon sources emerges as a strategic approach to improving the soil health of less fertile alkaline calcareous soils.
Keywords: Soil fertility; microbial dynamics; CO2 evolution; CO2 emission; Compost